Pelatihan Kewirausahaan Melalui Pembuatan Produk Kue Bagi Guru Kewirausahaan SMK Se-Jakarta Selatan - Rahmat Kusnedi (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
The availability of skilled workers, specially high school graduates such as vocational schools are needed for the operation of infrastructure that will be built by the government, but in reality the results of vocational graduates do not have the capabilities and competencies that match the needs. The lack of competition among vocational high school students is also derived from the lack of competencies held by teachers as teaching staff, Nearly 80 percent of vocational teachers are normative teachers who teach Indonesian, English, Religion and PKN so that only six percent of national education output is able to compete in an global competitive. One of the subjects where teacher competition is lacking in practice is entrepreneurship and causes students to only receive learning in the form of theory, from the statement above the Pradita Institute culinary arts program initiative to provide training for vocational entrepreneurship teachers, training in the form of PkM is conducted in cooperation with Teacher Consultation on Entrepreneurship Subjects in South Jakarta. PkM activities are designed with short teaching methods and practices, training practices are focused on training in making cake products. The implementation of PkM activities took place at Gedung B Pradita Institute, training on making cake products including; chocolate chips, onde-onde, swiss roll and talam ubi. It is hoped that through this PkM the teachers will be able to add competence and teach back to their students. This PkM activity is able to spur their enthusiasm to become an entrepreneur and be useful for partner economies. Keywords: Teacher, Entrepreneur, SMK, Cake, Culinary